Predisposing, Enabling, and Reinforcing Factors of E-cigarette Use among Junior High School Students in Yogyakarta, Indonesia - Heni Trisnowati; Yuningrum, Hesti (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: The number of e-cigarette users has increased tenfold over the past ten years. The prevalence of e-cigarette use continues to increase, especially among students. Objective: This study aims to identify factors that encourage the use of e-cigarettes among junior high school students in Yogyakarta City. Methods: This study used a cross-sectional survey approach with a sample size of 582 taken using a proportional stratified random sampling technique. Data were collected through a structured questionnaire, including respondent characteristics (gender, and age) as well as predisposing, enabling, and reinforcing factors for e-cigarette use. Data were analyzed using a chi-square test for bivariate analysis and a logistic regression test for multivariate analysis. Results: The results showed that knowledge (RP=4.06, CI 95%=1.60-10.3, p<0.05), affordability (RP=2.46, CI 95%=1.37-4.39, p<0.05), family members smoking (RP=3.14, CI 95%=1.62-6.09, p<0.05), peers smoking (RP=8.14, CI 95%=3.92-16.9, p<0.05) were associated with the use of e-cigarettes in students. Meanwhile, the availability of cigarettes is not significant with the use of e-cigarettes in students (RP=1.98, CI 95%=0.96-4.09, p>0.05). The results of multivariate analysis showed that the most influential factor in the use of e-cigarettes was peer smoking behavior. Conclusion: There is a relationship between knowledge, affordability, smoking family members, and smoking peers with the use of e-cigarettes in students. Health promotion programs on the dangers of e-cigarette use and how to avoid them should be implemented, as well as restrictions on access to e-cigarettes through the implementation of smoke-free areas in schools.